Propriedades estruturais e estudos fotoluminescentes de complexos B-dicetonatos nas regiões do visível e infravermelho próximo - Arruda, Joaldo Garcia (2019)
This work reports the synthesis, characterization and the study of spectroscopic and structural properties of trivalent lanthanide complexes presenting the following formulas, [Ln(dpm)3(tppo)], [Ln(dpm)2(NO3)(tppo)2] and [Ln (tppo)3(NO3)3], where Ln = Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb. The synthesized compounds were characterized by complexometric titration with EDTA, CHN elemental analysis, Fourier-transform infrared (FTIR) and RAMAN spectroscopies, thermogravimetric analysis (TGA) and single crystal X-ray diffraction. The results were in agreement with the suggested formulas and evidenced that the coordination of the -diketonate and NO3- ligands occur in a bidentate chelating form, while the phosphine oxide act as monodentate ligands. X-ray diffraction data by the single-crystal method indicate that the complex [Ln(dpm)2(NO3)(tppo)2] crystallizes in the space group P21/c with the following cell parameters: a = 71.073, b = 14.7665 (5), c = 18.0396 (6),  = 22.6660 (9),  = 90 and  = 103.5310 (10). The coordination polyhedron can be described by a distorted dodecahedron with local symmetry close to the point group D2d. The photoluminescent properties in the region of visible and near infrared (NIR) were investigated from the emission and excitation data. Excitation spectra are characterized by the presence of broad bands associated to transitions in the ligands (S0→S1), evidencing the efficient process of sensitization of the luminescence by the ligand. Emission spectra are characterized by narrow bands derived from the intraconfiguration-4fN hypersensitive transitions, such as Pr3+, 3H4→3F2; Nd3+, 4I9/2→4G5/2; Sm3+, 6H5/2→4F3/2; Dy3+, 6H15/2→6F11/2; Ho3+, 5I8→5G6; Er3+, 4I15/2→2H11/2; and Tm3+, 3H6→1G4. The results suggest that these compounds are potential candidates to act as optical amplifiers, luminescent markers, Light-converting molecular devices and chemosensors.